O uso de gamificação no ensino da ferramenta de Linha de Balanço - Correa, Cecília Carniello (2024)
The low level of knowledge of lean principles and tools by professionals in the construction industry may be attributed to the absence of a specific content approach during their training process. Therefore, the adoption of gamification as a teaching strategy could help enhance training effectiveness, increase interest, and improve retention of learning among participants. Supporting this perspective, this dissertation conducts an experiment with undergraduate students in Civil Engineering at the Federal University of São Carlos, combining gamification with traditional lectures. This study aims to assess the impact of gamification on the teaching of the Line of Balance (LOB) tool, which was adopted by the lean philosophy. To achieve this goal, a pilot experiment was conducted to validate data collection instruments and the game application method. Following the analysis and necessary corrections, a second application was conducted. Data for the research was gathered through two knowledge tests (quantitative analysis) and three qualitative questionnaires. Participants were divided into a control and intervention group to compare the traditional teaching method (control) and this method combined with gamification (intervention). Statistical analysis of the collected data revealed that students in the intervention group achieved better results in the tests. It was also noted that students participated much more actively and showed significantly higher engagement in the gamified class compared to the traditional lecture. The results indicate the positive influence of the use of gamified approaches in teaching LOB. The experiment demonstrated the feasibility of integrating gamification into the classroom, offering potential benefits to the construction industry at large.